2012
DOI: 10.3109/10408444.2012.725028
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology of dimethyl and monomethyl derivatives of acetamide and formamide: a second update

Abstract: Dimethylacetamide (DMAC) and dimethylformamide (DMF) continue to be important, widely used solvents involved in a wide variety of industrial applications. As liquids with relatively low vapor pressures, contact with both the integumentary and respiratory systems is the main source of human exposure. Although airborne control levels for the workplace have been established and industrial hygiene practices to limit dermal contact have been put in place, use of these chemicals has been associated with occupational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 161 publications
0
23
1
Order By: Relevance
“…Intake of DMF may be mainly from inhalation of its vapor and by physical contact with skin, and occupational exposure to DMF may cause nausea, abdominal pain, and alcohol intolerance (2). Especially, DMF has been shown to induce hepatotoxicity and liver dysfunction in animals and humans by many investigators, and it is known that the primary target organ of DMF is the liver in animals and humans (3-5). DMF is hydroxylated at its methyl moieties by the cytochrome P-450 (CYP) to produce N-methyl-N-hydroxymethylformamide (DMF-OH), the generated DMF-OH being biotransformed to N-methylformamide (NMF) by a non-enzymatic or enzymatic reaction, undergoing further reactions that result in xenobiotic enzymes (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Intake of DMF may be mainly from inhalation of its vapor and by physical contact with skin, and occupational exposure to DMF may cause nausea, abdominal pain, and alcohol intolerance (2). Especially, DMF has been shown to induce hepatotoxicity and liver dysfunction in animals and humans by many investigators, and it is known that the primary target organ of DMF is the liver in animals and humans (3-5). DMF is hydroxylated at its methyl moieties by the cytochrome P-450 (CYP) to produce N-methyl-N-hydroxymethylformamide (DMF-OH), the generated DMF-OH being biotransformed to N-methylformamide (NMF) by a non-enzymatic or enzymatic reaction, undergoing further reactions that result in xenobiotic enzymes (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Several chemicals that were present in the samples analyzed in the present study have been shown to exhibit toxic properties after acute or repeated exposure to skin, liver, kidneys, the CNS, the gastrointestinal tract, blood, and lungs, including developmental toxicity, corrosivity, and skin sensitization (Middaugh et al 2002;Kennedy 2012;PubChem 2017;ChemicalBook 2017;USEPA 2017). Genotoxic and tumor-promoting substances were also present (Horton et al 1965;PubChem 2017).…”
Section: Discussionmentioning
confidence: 91%
“…2,2,4‐Trimethyl 1,3‐pentanediol is a developmental toxicant with acute dermal and respiratory toxicity (PubChem ). N ‐Methylthioformamide is a developmental toxicant with acute dermal, respiratory, and liver toxicity (Kennedy ). Tetramethylbutanedinitrile is acutely toxic by the oral, dermal, and inhalation routes (PubChem ).…”
Section: Resultsmentioning
confidence: 99%
“…Metabolic intermediates formed by xenobiotic metabolizing enzymes are known, in most cases, to have a larger effect on human toxicity than the original chemical itself. DMF, which is widely used in the industry (15) , is known to largely affect the liver (16) , where the metabolic intermediate N-methylforamide (NMF) is produced during metabolism with the xenobiotic metabolizing enzyme cytochrome P-450(CYP)2E1 acting as catalyst. NMF is reported to have greater toxicity than DMF (15) .…”
Section: Discussionmentioning
confidence: 99%